2017
DOI: 10.1109/tlt.2017.2740172
|View full text |Cite
|
Sign up to set email alerts
|

Review of Research on Student-Facing Learning Analytics Dashboards and Educational Recommender Systems

Abstract: This article is a comprehensive literature review of student-facing learning analytics reporting systems that track learning analytics data and report it directly to students. This literature review builds on four previously conducted literature reviews in similar domains. Out of the 945 articles retrieved from databases and journals, 93 articles were included in the analysis. Articles were coded based on the following five categories: functionality, data sources, design analysis, student perceptions, and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(192 citation statements)
references
References 33 publications
1
158
1
5
Order By: Relevance
“…Providing learners with visualizations of their progress enables them to reflect upon their learning, and an emerging body of research has begun to empirically evaluate the effectiveness of such feedback [1,2,6,10]. Over time, this reflection should improve learners' use of SRL strategies [3,8].…”
Section: Self-regulated Learning In Moocsmentioning
confidence: 99%
“…Providing learners with visualizations of their progress enables them to reflect upon their learning, and an emerging body of research has begun to empirically evaluate the effectiveness of such feedback [1,2,6,10]. Over time, this reflection should improve learners' use of SRL strategies [3,8].…”
Section: Self-regulated Learning In Moocsmentioning
confidence: 99%
“…Meta-analytical evidence suggests that properly designed SRL interventions can improve learning (Dignath & Büttner, 2008;Panadero, 2017;Sitzmann & Ely, 2011). Interventions to enhance students' SRL include, for example, self-assessment (Panadero & Alonso-Tapia, 2013;Panadero, Jonsson, & Botella, 2017), concept mapping (Gurlitt & Renkl, 2010;Nesbit & Adesope, 2006;Novak & Musonda, 1991), learning diaries (Klug, Ogrin, Keller, Ihringer, & Schmitz, 2011;Schmitz & Wiese, 2006), and learning analytics dashboards (Bodily & Verbert, 2017;Jivet et al, 2017;Sedrakyan et al, 2018). In this study, we are at the intersection of this knowledge base.…”
Section: Related Literaturementioning
confidence: 91%
“…Research literature related to learning analytics applications reveals that surprisingly little consideration has been given to which data is meaningful to collect; this is underlined by Winne's (2017) notion that out of several widely cited descriptions of learning analytics, none answer the question of which data should be gathered for input to methods that generate learning analytics. In a review of student-facing dashboards, Bodily & Verbert (2017) found that the most often used types of data in dashboards were (1) the number of times a resource was accessed (in 75% of articles), (2) data on student mastery as measured by assessment (in 37% of articles), and (3) data on time spent accessing resources (in 30% of articles). It is clear that the availability of data may affect which data is used in learning analytics.…”
Section: Introductionmentioning
confidence: 99%
“…First, as we have discussed in the IU and UMBC examples, we support student facing analytics or dashboards (Bodily & Verbert, 2017) that provide students with a perspective on where they currently stand, taking the approach of providing students with tools to orient them vs. a projected trajectory of predicted outcomes not yet realized. In fact, we like to say that predictive analytics should be used to identify at‐risk students, but never as a means to motivate them—by sharing the prediction as a fait accompli .…”
Section: A Middle Ground: Ethical Learning Analytics As “Choice Archimentioning
confidence: 99%